2017
DOI: 10.1016/j.jdermsci.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

FGF2-mediated attenuation of myofibroblast activation is modulated by distinct MAPK signaling pathways in human dermal fibroblasts

Abstract: Background Previous human and animal studies have demonstrated the ability of exogenously administered basic fibroblast growth factor (FGF2) to act as an antifibrotic agent in the skin. Though the activity of FGF2 as an anti-scarring agent is well-established for fibrotic skin wounds, the mechanisms by which FGF2 exerts these actions are not entirely understood. Canonical FGF2 signaling proceeds in part via FGFR/MAPK pathways in human dermal fibroblasts, and FGF2 has been described to prevent or reverse the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 60 publications
3
48
0
2
Order By: Relevance
“…Samples were processed and Western blot was performed using standard protocols as described previously (Dolivo et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were processed and Western blot was performed using standard protocols as described previously (Dolivo et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured in VisiPlate 24‐well plates (Perkin Elmer) until analysis. Cells were fixed and analyzed by immunofluorescence as described previously (Dolivo et al, ) and imaged on an Axiovert 200 M (Zeiss). Alternatively, cells were stained for FITC‐annexin V/PI according to manufacturer's protocols and analyzed on an Axiovert 200 M or an Accuri C6 flow cytometer (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…FGF2 is an interesting growth factor, which is known to inhibit fibroblasts activation in vitro by distinct signaling pathways such as Smad2/3 and MAPK pathways [15,16,18]. The differentiation and activation of hPSCs into CAF-like myofibroblasts is mainly induced by TGF-β as a result of the interaction with cancer cells within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Activation and differentiation of PSCs into myofibroblastic CAFs is commonly regulated by Transforming growth factor beta (TGF-β) [13]. In literature, fibroblast growth factor 2 (FGF2, 17.2 kDa) has been shown to exert inhibitory effects against TGF-β [ [14][15][16][17][18]. The activation of extracellularregulated kinase 1/2 (ERK1/2) pathway by FGF2 has been shown to counteract the TGF-β mediated activation in endothelial cells or fibroblasts [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Our lab recently demonstrated that FGF2 was able to inhibit TGF-β1-mediated activation of several lines of primary adult and neonatal human dermal fibroblasts, and that this inhibition could be abrogated by treatment with small molecule inhibitors of ERK and JNK but not of p38. We also demonstrated that treatment with ERK or JNK inhibitor in the absence of exogenous FGF2 was sufficient to induce fibroblast activation, potentially implicating basal activation of these pathways in the promotion of myofibroblast phenotypes, or implicating well-established cross-talk between MAPK and TGF-β signaling more generally in this process [69]. Taken together, these data suggest that FGF2 has the ability to prevent or reverse fibroblast activation via various cellular pathways and mechanisms that are likely context-dependent.…”
Section: Evidence For Fgf2 As An Antagonist Of Myofibroblast Differenmentioning
confidence: 99%